Economical and sustainable pavements - The EcoLanes project - Pilakoutas, Kypros; Neocleous, Kyriacos; Angelakopoulos, H.; Koutselas, K. (My University, 2010)
A European research project EU FP7 Specific Targeted Research Project (STREP) EcoLanes has been undertaken to develop pavements using concrete reinforced with recycled steel tyre-cord fibers (RSTCF). Using RSTCF and industrially produced steel fibers, EcoLanes developed concretes suitable for wet consistency and RCC. Following extensive numerical and analytical work, a design framework and software were developed by UTI for use by design engineers. Analysis and design tools were developed based on the concept of long-life rigid pavements (LLRPs) made with wet/dry SFRC. Methodologies were developed for the LCA (life-cycle analysis) of LLRPs made with wet and dry SFRC. The construction of the demonstration pavements confirmed that the developed technology can be easily applied in practice.
Keywords: Concretes; Rollers (machine components); Roller-compacted concrete